Surgical trauma induces overgrowth in lower limb gigantism: regulation with use of rapamycin is promising. (4th January 2018) - Pinto, Rohan Sebastian; Harrison, William David; Graham, Kenneth; Nayagam, Durai
Abstract : We describe an unclassified overgrowth syndrome characterised by unregulated growth of dermal fibroblasts in the lower limbs of a 35-year-old woman. A PIK3CA gene mutation resulted in lower limb gigantism. Below the waist, she weighed 117 kg with each leg measuring over 100 cm in circumference. Her total adiposity was 50% accounted for by her legs mainly. Liposuction and surgical debulking were performed to reduce the size of the limbs but had exacerbated the overgrowth in her lower limbs. Systemic sepsis from an infected foot ulcer necessitated treatment by an above-knee amputation. Postoperatively, the stump increased in size by 19 kg. A trial of rapamycin to reverse the growth of the stump has shown promise. We discuss the clinical and genetic features of this previously unclassified disorder and the orthopaedic considerations involved.